THE EFFECT OF ROE, LDR, NPL AND BOPO ON STOCK PRICES OF CONVENTIONAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2020–2024 PERIOD - Sara, Yuni; Chaidir, Mohamad; Yulianti, Grace (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2025)
This study aims to analyze the effect of Return on Equity (ROE), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), and Operating Expenses to Operating Income (BOPO) on the stock prices of conventional commercial banks listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The research population includes all conventional commercial banks on the IDX, with a sample size of 25 banks selected using purposive sampling. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results show that ROE and NPL have a significant positive effect on stock prices, while LDR and BOPO have a significant negative effect. The positive effect of NPL indicates that during the pandemic and economic recovery period, investors viewed the increase in non-performing loan ratios as a manageable risk due to the effectiveness of bank credit restructuring policies. These results are in line with signaling theory, which explains that financial information serves as a signal for investors in assessing a company's prospects.